2019
DOI: 10.30871/jaic.v3i1.1051
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Sistem Absensi Sekolah Menggunakan Fingerprint Terintegrasi Dengan Smartphone Android

Abstract: The need of student attendance information in schools is a major factor in success of the academic process. Often there are validation and identification errors in the student attendance process (human error or manipulation process) as well as the slowness of information obtained, since the attendance is recorded manually in each class. This has an impact on success of the academic process directly and the community at large. Because the importance of attendance information, various studies have offered the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
1
0
5
Order By: Relevance
“…The result of research that most PAI teachers have been disciplined in time in carrying out their obligations [5]. Another research conducted that online attendance using smartphones is used to monitor student attendance by parents and teachers [6]. In line with this research, Faradilla also revealed that android-based online attendance makes it easier for teachers to attend students and calculate the number of student attendance [7].…”
Section: Introductionmentioning
confidence: 81%
“…The result of research that most PAI teachers have been disciplined in time in carrying out their obligations [5]. Another research conducted that online attendance using smartphones is used to monitor student attendance by parents and teachers [6]. In line with this research, Faradilla also revealed that android-based online attendance makes it easier for teachers to attend students and calculate the number of student attendance [7].…”
Section: Introductionmentioning
confidence: 81%
“…Di penelitian lainnya, penerapan fingerprint menggunakan android memang cukup efektif untuk memvalidasi kehadiran [11]. Akan tetapi setiap perangkat android dapat didaftarkan hingga 5 data biometric fingerprint.…”
Section: Metode Penelitianunclassified
“…Sistem kehadiran yang baik akan meningkatkan tingkat produktifitas kerja dan profit organisasi [4]. Salah satu teknologi yang dapat dipercaya dalam validasi kehadiran adalah menggunakan fingerprint [5]. Sistem absensi fingerprint dibuat untuk mempermudah pendataan kehadiran karyawan atau staff dalam menjaga produktifitas perusahaan [6].…”
Section: Pendahuluanunclassified